The changing face of liver biospy in clinical practice. (13th March 2011) - Mandair, D S; Bridgestock, H; Mutimer, D; Freshwater, D; ,
Abstract : Introduction: As liver biopsy remains on the GI Curriculum we audited practice in University Hospital Birmingham before and after the introduction of Fibroscan, and practice in other Trusts in the region. Methods: An online survey was sent to all gastroenterology consultants and trainees in the West Midlands. Liver biopsies were audited at UHB before and after introduction of Fibroscan, excluding targeted, transjugular and time-zero biopsies. Results: 174 biopsies were performed Feb 2008–July 2008 (M102/F74), age range 18–77. 88 blind, 86 USS guided. 123 biopsies were performed Feb 2009–July 2009 (M76/F47) age range 20–82. 54 blind, 69 USS guided. Blind biopsies fell from 50.6% to 43.9%. Hep C biopsies fell from 14.3% to 4.9%. Failed blind biopsies rose from 6 to 12. 55 people responded to the survey (12 consultants/43 trainees). Only 17/55 had made any request for blind liver biopsies in the last 12 months. 77.4% had preformed last than 10 biopsies in the last year while 30% had performed less than 10 lifelong. 59.4% still felt that blind percutaneous biopsy was still an important technique. Conclusion: Fibroscan reduced the number of Liver biopsies performed. Blind percutenous liver biopsy experience is decreasing, and should no longer be a requirement in regional training programs.